Kinetics drying of blackberry bagasse and degradation of anthocyanins and bioactive properties - Grández-Yoplac D.E. (2021)
The process of drying food is necessary to preserve it; however, some bioactive compounds can be degraded during drying process. In this work, the convective drying process of Peruvian blackberry bagasse and the degradation of anthocyanins, total phenolic content (TPC), and antioxidant capacity (AC) were studied. The logarithmic model fitted well to the data and could predict the process, showing that 6 h of drying at 90?C is enough to reach equilibrium moisture. Anthocyanin degradation followed a first-order kinetic model with reaction rate constant between 5.45 × 10?2 ± 4.68 × 10?3 and 1.21 × 10?1 ± 2.31 × 10?2 h?1, and activation energy of 25.11 kJ/mol. The highest retention (84.38%) of anthocyanins was obtained in 1 h at 50?C and the highest degradation (68.54%) in 6 h at 90?C. The TPC and AC increased with the drying time and temperature due to the increased water evaporation. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.